Quality improvement project to reduce the incidence of nasal bridge pressure sores in adults requiring acute non-invasive ventilation (NIV) and continuous positive airway pressure (CPAP) - Adam Rochester (BMJ Open Quality)
Non-invasive ventilation (NIV) and continuous positive airway pressure (CPAP) use positive airway pressure delivered via a tight-fitting mask to treat respiratory failure. In the acute setting, the mask covers the nose and mouth with various interface options. National guidelines indicate that NIV use should be targeted for close to continuous use in the first 24 hours.Research has shown that some oro-nasal masks can generate pressures between 6.37 and 12.2 kPa on the nasal bridge when adjusted to minimise mask leak, essential in reducing patient-ventilator asynchrony. Research has also shown that tissue damage and necrosis can occur after just 2 hours of pressure-induced ischaemia at a pressure of 4.6 kPa, demonstrating this patient cohort’s high risk of developing a medical device-related pressure injury (MDRPI).Baseline data from October 2021 onwards identified eight nasal bridge pressure ulcers reported via the Trust’s incident reporting system. Five were classified as suspected deep tissue injury, and three were classified as category 2. No ulcers were scored at category 3 or worse.This project used the Plan Do Study Act (PDSA) approach to prevent any new nasal bridge pressure ulcer derived from using NIV or CPAP therapy for any patient admitted to our hospital site for 40 days from 1 November 2022. Using four PDSA cycles, there was a statistically significant reduction in the frequency of category 2 MDRPIs caused by NIV mask interfaces for 1466 ‘NIV days’ across 19 calendar months.